2017
DOI: 10.4149/bll_2017_051
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiogenic cytokines (VEGF-A and VEGF-C) and clinical characteristic in women with unexplained recurrent miscarriage

Abstract: INTRODUCTION: Recurrent miscarriage (RM) defi ned as 2 or more spontaneous miscarriage before 20 weeks of gestation, affects at least 1 % of couples trying to conceive. In over 50 % of cases, the cause of the loss of pregnancy remains unexplained. Reduced expression of Angiogenic factors such as: vascular endothelial growth factor (VEGF-A) and VEGF-C has been linked with spontaneous miscarriage, likely due to defective foetal and placental angiogenesis. AIMS AND OBJECTIVES: To investigate the relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
12
1
1
Order By: Relevance
“…2729 . Lower maternal level of VEGF was observed in unexplained recurrent miscarriage compared to those in healthy and pregnant women 30 . The secretory phase of the uterus is the vascular maturation period, which expresses more VEGF than in the proliferative phase during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 74%
“…2729 . Lower maternal level of VEGF was observed in unexplained recurrent miscarriage compared to those in healthy and pregnant women 30 . The secretory phase of the uterus is the vascular maturation period, which expresses more VEGF than in the proliferative phase during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 74%
“…However, the evidence of the link between inflammation and miscarriage in women with early threatened abortion is limited. Given that the similar maternal-fetal pathological changes between threatened abortion and miscarriage [17,18], we speculated that inflammation might be associated with pregnancy outcome in the early threatened abortion.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF also known as vascular permeability factor (VPF), is an important angiogenetic cytokine. It regulates proliferation, differentiation, and survival of endothelial cells and enhances vascular permeability [25]. It was shown that the overexpression of vascular VEGF is an outstanding manifestation in the course of RBI [26].…”
Section: Discussionmentioning
confidence: 99%